The Effect of Epidermal Growth Factor on the Outcomes of Myringoplasty - Bongale, Kiran Ravindranath; Bhat, Vikram Kemmannu; Yadav, Mona (Annals of Otology and Neurotology, 2020)
Introduction Chronic otitis media is a widespread disease of developing countries. The burden of the disease continues to be high and so is the demand for surgical myringoplasty. This pilot study aimed to compare in adults the outcomes of myringoplasty with and without the application of epidermal growth factor gel (EGF) with respect to the time taken for graft uptake, improvement of hearing, and complications.Materials and Methods This randomized controlled study was undertaken in a tertiary referral public hospital in a span of 2 years with a sample size of 60 patients. All of them underwent diagnostic nasal endoscopy, otoendoscopy, and pure tone audiometry and treated with conventional underlay myringoplasty using temporalis fascia (Group A—30 cases with EGF, Group B—30 controls without EGF). Patients were followed-up at 15, 30, 90 days postoperatively.Results The average time taken for closure of tympanic perforation and graft uptake by group A was lesser than group B. This difference was found to be statistically significant. Residual perforation at 1 month was commoner in group B as compared with group A. The final improvement of the hearing was the same in both the groups in the healed cases.Conclusion The EGF can be used to improve the outcomes of myringoplasty. It can hasten the closure of tympanic membrane perforation and increase the success rates of the surgery.
Keywords: chronic otitis media; myringoplasty; epidermal growth factor; hearing loss